An Exact Solution for a Single Machine Scheduling Under Uncertainty - Rebaz Abdulla Sharif; Ayad M. Ramadan (Jambura Journal of Mathematics, 2023)
Here we have n jobs on one machine where the processing times are triangular fuzzy numbers. The jobs are available to process without interruption. The purpose is to find a best sequence of the jobs that minimizes total fuzzy completion times and maximum fuzzy tardiness. In this paper a new definition is presented called D-strongly positive fuzzy number, then an exact solution of the problem through this definition is found. This definition opens new ideas about converting scheduling problems into fuzzy cases.